Waqf fundraising management: a proposal for a sustainable finance of the Waqf institutions - Shulthoni, Muhammad; Md Saad, Norma; Kayadibi, Saim; Ariffin, Muhammad Irwan (Bank Indonesia Institute, 2018)
This paper studies the theoretical structure of financing for Islamic philanthropy in the form of waqf or endowment by looking at the past and present forms of waqf. Waqf is expected to play a more important role to tackle current social and educational issues, where financial sustainability has become one of the greatest challenges faced by waqf institutions. Using the content and thematic analysis approaches, this paper reviews the practice of successful waqf institutions and summarizes the features that are significant to a successful waqf fundraising and management. The paper analyses three models that are suitable for innovation and management of waqf fundraising: Venture Philanthropy of Waqf Model (VPWM), Value-Based Capital Model of Waqf (VBCM), and Social Enterprise Waqf Fund Model (SEWF). The paper then investigates the possibility of applying the Management by Objectives (MBO) framework to improve the overall management of waqf institutions. The discussions are hoped to be able to contribute towards developing a better fundraising and management of waqf institutions.